'Up with People' elevates Atwater (Raton Range Raton, New Mexico)
Newspaper Article on Tammy Atwater and her opportunity to participate in the UP with people program.
Master list item #: 43
File location is in the Raton File Cabinet
Keywords: Atwater, Tammy; Atwater, David; Atwater, Mary; Belk, J. Blanton; Up with people program; New Mexico State University; Liberty Federal Savings Bank; International State Bank; Sunwest Bank; Local History; Biography; Life and Customs; Performance; Public service activities; Education; Educational Programs; Raton, New Mexico; Las Cruces, New Mexico; Tucson, Arizona